Reduction of adhesive wear with use of tool coating reducing thermoelectric currents. Issue 1 (1st May 2022) - Schrepfer, A; Schott, A; Tröber, P; Keunecke, M; Welm, M; Steinlehner, F; Golle, R; Volk, W
Abstract: Blanking is one of the main processes in producing sheet metal components. The impact of adhesive wear of the blanking tools on the cost efficiency is high, especially when processing aluminum. As an influencing factor on adhesive wear in blanking, thermoelectric currents have been considered to a very small extent. Recent investigations have shown that thermoelectric currents occur in every blanking tool due to the rise of temperature in the shear zone in interaction with a difference of the material-specific Seebeck coefficients of tool and sheet metal. A reduction in the amount of wear was observed in case of a smaller difference of Seebeck coefficients and therefore lower levels of flowing thermoelectric currents. This paper follows the approach of adjusting the Seebeck coefficient of the tool material CF-H40S+ to the one of the sheet material by means of coating with CrAlN, in order to reduce the flowing thermoelectric currents and consequently adhesive wear. For this purpose, the effect of coating on the Seebeck coefficients, the thermoelectric currents during blanking as well as resulting wear quantities were investigated. Basic correlations could be revealed.